The network paradigm of the 21st century and its key technologies. - Moridera, A. (IEEE Communications magazine)
This article proposes a network paradigm called the single-server-view network as the basis for networks in the 21st century, when the value of a network to users will be based on the services provided rather than data communication capability. Based on our paradigm, we propose a double-plane network architecture, consisting of a simplified data forwarding plane and a service control plane, that performs all the complex processing tasks. The data forwarding plane uses an advanced photonic network as its basis. The service control plane consists of agent, service, and policy control layers with open interfaces between layers. Leading-edge information processing technologies, such as active node, agent, distributed processing, and policy-based management, are used in this plane. Since mobile communication is becoming a major access technology, an approach to integrating mobile and fixed networks into this framework is also proposed. The current status of key technologies, such as photonic networks, agent technology, and policy-based management, are reported.